1993
DOI: 10.1139/f93-050
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bacillus thuringiensis var. israelensis Larvicidal Activity and Its Distribution in Benthic Substrates and Hyporheic Zone of Streams

Abstract: Numerous field trials have indicated that the effectiveness of Bacillus thuringiensis var. israelensis (B.t.i.) is limited to a short distance in streams, but the reasons for loss of toxicity have not been identified. Two streams were treated with B.t.i. and experiments were conducted to monitor the transfer of B.t.i. toxicity from the channel water to different compartments within the stream. These compartments included benthic substrates such as sediments, periphyton covering bedrocks, vegetation (moss and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…These results indicated that the Bti crystals had been adsorbed by the algae growing on rocks. This interaction was later con® rmed by Tousignant et al (1993) who found that periphyton collected after a Bti treatment (overdosage) was highly toxic to mosquito larvae, but they could not detect any toxic activity associated with sedimented matter.…”
Section: Fate Of Bti Toxic Activity In the Environmentmentioning
confidence: 94%
See 2 more Smart Citations
“…These results indicated that the Bti crystals had been adsorbed by the algae growing on rocks. This interaction was later con® rmed by Tousignant et al (1993) who found that periphyton collected after a Bti treatment (overdosage) was highly toxic to mosquito larvae, but they could not detect any toxic activity associated with sedimented matter.…”
Section: Fate Of Bti Toxic Activity In the Environmentmentioning
confidence: 94%
“…Back et al (1985) showed that two chironomid genera (Diptera) that normally feed on organic debris, and blepharicerid larvae (Diptera) which feed by scraping periphyton growing on rocks, were adversely aVected after a Bti treatment thereby suggesting that Bti toxic crystals were attached to these substrates. Tousignant et al (1993) found that, after treating a small stream with Bti, high percentages of mortality were obtained when periphyton samples were tested against mosquito larvae, indicatin g that Bti toxic particles were associated with this substrate.…”
Section: Factors Avecting Bti Activity Against Black Fliesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, its insecticidal activity can be tested by performing bioassays using environmental samples (i.e., water, soil, or leaf litter samples, etc.) (9,38,44). Unfortunately, the sensitivity of this approach is often too low to detect slight modifications of toxicity, as B. thuringiensis usually does not exhibit a high level of residual activity (36).…”
mentioning
confidence: 99%
“…There are several possible explanations, including entrapment of B.t.i. particles by moss (Tousignant et al 1993), or stagnation in slower pools with a gradual release over time.…”
Section: Resultsmentioning
confidence: 99%